Differences in Learning Outcomes Mathematics Student Using the Jigsaw Method and Contextual Teaching Learning in the Principal Discussion Rectangular Flat Building - Tambunan, Yusniar N; Siregar, Christyani; Situmorang, Titin Elfrida (International Journal of Educational Research Excellence (IJERE), 2024)
Study This aim for know difference results Study taught students use method Jigsaw and Contextual Teaching Learning methods in the main discussion Get up flat facet four. Data analysis to test hypotheses with formulas t test statistics. The type of research used is experimental research. From the two sample groups, one experimental group 1 was determined , namely class VIII b and one experimental group, namely class VIII c , both groups were given the same instruments. Where are the instruments totaling 10 items the most important question formerly tried out For know validity , reliability , level difficulty and distinguishing power . Based on The results of the research data state that the learning outcomes of the two sample groups are different. After carrying out the requirements test, namely the normality test using the Liliefors test using the Jigsaw method, it was obtained that L 0 = 0.1342 and L table = 0.161, with the CTL method, L 0 = 0.1232 and L table = 0.161 were obtained from the two samples L 0 < L table and both classes have a normal distribution and the homogeneity test with the variance comparison test obtained F Hit = 2.26 and F table = 2.424, so F Hit < F table then both classes have homogeneous variance. The hypothesis is tested with the t test and the real level α = 0, 05 obtained t hit = 0.885 and t tab = 2.019 it turns out that t hit < t tab , t hit is outside the acceptance of Ho so Ho is rejected, meaning there is a significant difference between the learning outcomes of students taught using the Jigsaw method and the CTL method in building materials rectangular flat.